PERUBAHAN TUTUPAN LAHAN KAWASAN HUTAN DI WILAYAH UPT KPH BENGKAYANG - WILAYAH RESORT PENGELOLAAN HUTAN (RPH) I DAN II TAHUN 2013, 2017 DAN 2021 - Lestariningsih, Siti puji; Mulyono, Joko Tris; Widiastuti, Tri (Universitas Tanjungpura, 2023)
The Forest Management Unit (KPH) Bengkayang is a forest management unit located in the province of West Kalimantan, consisting of three forest management resort areas (RPH): RPH Region I Suti Semarang, RPH Region II Lumar, and RPH Region III Siding. The observed decline in the function and potential of the forest aligns with the reduction of maintainable forest areas due to forest degradation resulting from activities such as large-scale logging for agricultural expansion, mining, and transmigration carried out by the local communities around the forest. The aim of this research is to analyze the changes in the forest area in UPT KPH Bengkayang, specifically in the RPH I and II regions, for the years 2013, 2017, and 2021. The research methodology involves remote sensing techniques with visual interpretation classification of Landsat 8 OLI and TIRS images. There are six land cover categories in UPT KPH Bengkayang, RPH I and II: secondary dryland forest, mixed cultivation of dryland and shrubs, shrubland, open land, water bodies, and rice fields. During the period from 2013 to 2017, a significant reduction occurred in secondary dryland forest, covering an area of 316.18 ha (1.89%), while mixed cultivation of dryland and shrubs increased by 415.97 ha (0.67%). In the period from 2017 to 2021, the largest reduction occurred in shrubland, amounting to 469.49 ha (82.06%), while mixed cultivation of dryland and shrubs showed the highest increase at 566.64 ha (0.96%).Keywords: Bengkayang forest management unit, Deforestation, Forest area, Land cover change, Landsat imagery.AbstrakKesatuan Pengelolaan Hutan (KPH) Bengkayang merupakan unit pengelolaan hutan yang berlokasi di provinsi Kalimantan Barat, terdiri dari tiga wilayah resort pengelolaan hutan (RPH): RPH Wilayah I Suti Semarang, RPH II Wilayah Lumar, dan RPH III Wilayah Siding. Fenomena menurunnya fungsi dan potensi hutan sejalan dengan menyusutnya luas kawasan hutan yang dapat dipertahankan disebabkan oleh degradasi hutan akibat aktivitas seperti penebangan besar-besaran untuk pembukaan pertanian, penambangan, dan transmigrasi yang dilakukan oleh masyarakat di sekitar hutan. Tujuan penelitian ini adalah untuk menganalisis perubahan luas kawasan hutan di UPT KPH Bengkayang wilayah RPH I dan II pada tahun 2013, 2017, dan 2021. Metode penelitian menggunakan teknik penginderaan jauh dengan klasifikasi interpretasi visual Citra Landsat 8 OLI dan TIRS. Enam kategori tutupan lahan di UPT KPH Bengkayang wilayah RPH I dan II meliputi hutan lahan kering sekunder, pertanian lahan kering campur semak, semak belukar, lahan terbuka, tubuh air, dan sawah. Selama periode tahun 2013-2017, terjadi penurunan signifikan pada hutan lahan kering sekunder sebesar 316,18 ha (1,89%), sementara pertanian lahan kering campur semak mengalami peningkatan mencapai 415,97 ha (0,67%). Pada periode 2017-2021, terjadi penurunan terbesar pada semak belukar sebesar 469,49 ha (82,06%), sementara pertanian lahan kering campur semak mengalami peningkatan tertinggi sebesar 566,64 ha (0,96%).Kata kunci: Kesatuan Pengelolaan Hutan Bengkayang, Deforestasi, Kawasan Hutan, Perubahan Penutupan Lahan, Citra Landsat.